Designing and planning for the active use of public spaces in downtown Kansas City, Missouri - Seaman, Zachary Neil (Kansas State University, 2012)
Kessler’s 1893 parks and boulevards system was established to spur investment. The 1893 Report shaped the present city pattern and form of Downtown Kansas City by encouraging decentralized city and metropolitan growth. Today’s system discourages pedestrian mobility and accessibility through the design and context of the public spaces. Since walkability contributes to successful public spaces, walking for transportation to encourage active use could improve today’s open-space system. To address the present condition facing the system, the report analyzes the morphology of Kessler’s parks and boulevards system within the 2010 Greater Downtown Area Plan boundary. For methods, stakeholder notes and professional interviews explain the planning process behind the 2011-2012 KCDC project to revitalize public space. The stakeholder notes and professional interviews assess the context of the Kansas City Design Center’s vision to revitalize Kessler’s parks and boulevards system. Using the StreetSmartTM walkability model, the design and context of public space can help revitalize Kessler’s 1893 system and today’s park system. The model can be used to measure and prioritize investment by assessesing the pedestrian mobility and accessibility of public spaces. The implication of the report is that if the design and context of public spaces addresses the public interest and walkability, public spaces will become connected, diverse, market-competitive, and actively used. Short-term pedestrian amenities and long-term infrastructure improvements provide different ways to prioritize pedestrian mobility and accessibility to create a walkable downtown, one of the goals of the Greater Downtown Area Plan.
Keywords: Walkability; Park design; Public interest; Park planning; Geographic information systems; Area Planning and Development (0341); Design (0389)